Dampak Penghapusan Pupuk Subsidi Bagi Petani Kelapa Sawit Swadaya Setelah Disahkannya Peraturan Menteri Pertanian No 10 Tahun 2022 tentang Tata Cara Penetapan Alokasi Dan Harga Eceran Tertinggi Pupuk Bersubsidi Sektor Pertanian - Alamanda, Asri Elies; Mangar, Irma (Wajah Hukum, 2024)
Palm oil or crude palm oil (CPO) is one of Indonesia's leading export commodities. The high level of exports is not accompanied by the provision of subsidized fertilizer for independent community farmers. Through the Ministry of Agriculture (Kementan) it has decided to remove subsidized fertilizer for oil palm plantations. With the elimination of fertilizer subsidies for oil palm farming, it makes it difficult for farmers to meet their fertilizer needs. The policy of eliminating subsidized fertilizer assistance has a direct impact on the productivity of oil palm farmers. The problems studied are limited to: What impact will there be after the ratification of the Minister of Agriculture Regulation No. 10 of 2022 concerning Procedures for Determining the Allocation and Highest Retail Prices for Subsidized Fertilizers in the Agricultural Sector related to the elimination of fertilizer subsidies for oil palm plantations? and How to overcome the problem of no subsidized fertilizer for oil palm farmers? The research method used is the Empirical Juridical method. The research results show that there are many impacts that can occur with the elimination of subsidized fertilizers by the government, especially for oil palm plants. Fluctuating CPO prices tend to make farmers unable to predict their income and set aside to purchase non-subsidized fertilizer which is unaffordable. Then the countermeasure initiated by the government is to use organic fertilizer, but it can take a long time to process organic fertilizer and the results can only be seen one year later. This is different from chemical fertilizers where the results can be seen immediately in a matter of months.